Hi there! :)
Answer:
Choice D. (y - 4) = 3(x + 2)
Step-by-step explanation:
An equation in point-slope form is:
(y - y1) = m(x - x1)
Where:
y1 = y-coordinate of a point
m = slope
x1 = x-coordinate of a point
In this instance, the point given is (-2, 4) with a slope of 3. Therefore, the equation in point-slope form would be Choice D. (y - 4) = 3(x + 2)
Answer:
Step-by-step explanation:
answer is C
Because formula of equation of slop is
Y-y1=m(x-x1)
B: –3a^2 + 11a + 5
C: 3a^2 + 11a + 5
D: –3a^2 + 11a – 5
Answer: B = –3a^2 + 11a + 5
For difference, the answer is
-3a^2 -5a -5
Step-by-step explanation:
(3a – 3a^2) + (5 + 8a)
To find the sum or difference, we will open the brackets.
To look for l the sum, we add
3a – 3a^2 + 5 + 8a
Collecting like terms,
= -3a^2 +8a + 3a +5
= -3a^2 + 11a + 5
Option B is the right answer.
To look for the difference, we subtract.
(3a – 3a^2) - (5 + 8a)
Opening the brackets
3a – 3a^2 - 5 - 8a
Collecting like terms
-3a^2 + 3a -8a -5
= -3a^2 -5a -5
The options available corresponds only to what we got for the sum, so
-3a^2 + 11a + 5 is the answer
1.) Remove parentheses.
3a−3a^2 +5+8a
2.) Collect Like Terms.
(3a+8a) - 3a^2+5
3.) Simplify.
11a - 3a^2+5
tanx + cotx = 1/ sinxcosx
–7.12 = –4.8 + x
A.
–11.92
B.
–11.2
C.
–2.32
D.
2.32
Answer: -12x+20;
Step-by-step explanation: